Alterity and the evasion of justice : explorations of the "other" in world Christianity - Womack, Deanna Ferree; Barreto, Raimundo (World Christianity and public religion, 2023)
"This volume considers overlooked "others" in the field of World Christianity. Contributors point to gender, sexuality, and race as themes ripe for exploration, while also identifying areas that have fallen outside the dominant World Christianity narrative, such as the Middle East and postcolonial indigenous and aboriginal theological expressions"--